Advancing methods for comparative nutritional LCA of milk and plant-based milk substitutes - Kovanen, Immi; Kyttä, Venla; Kårlund, Anna; Pajari, Anne-Maria; Tuomisto, Hanna; Saarinen, Merja; Kolehmainen, Marjukka (SPRINGER HEIDELBERG, 2025)
Purpose
The contribution of milk on the environmental and nutritional impacts of diets is substantial especially in countries with high consumption rates of dairy products, such as in the Nordic countries. Due to environmental and health reasons, plant-based drinks (PBDs) are gaining popularity among consumers, but the nutritional composition of PBDs varies depending on their base ingredients and possible fortification. This study develops product group-specific nutrient indices to be used as functional units (nFU) in life cycle assessments (LCA) of milks and PBDs.
Methods
Here, we formed three product group-specific nutrient indices for milk and PBDs: (i) based on our previous development of product group-specific indices considering the current dietary role of milk in Finnish diets, (ii) based on the potential nutritional benefits of PBDs compared to milk, and (iii) as combination of the two abovementioned indices. The new indices were then applied as a nFUs in a case study comparing selection of 46 drinks from the Finnish food composition database including milks and fortified and unfortified PBDs. The environmental impacts were assessed in five different impact categories utilizing data from LCA databases.
Results and discussion
The index based on current consumption led to the highest nutrient index scores for cow's milks and consequently lower environmental impacts when used as a nFU, whereas the index based on nutrients obtained from PBDs as nFU led to higher environmental impacts for milk and lower for PBDs. Cow's milk had the highest climate impact when the impacts were allocated per unit of mass, but in nFU-based comparison, some PBDs had higher impacts than cow's milk. The results showed notable difference between fortified and unfortified PBDs, as the environmental impacts of unfortified PBDs were higher than impacts of milk when the comparison was based on nutrient content, while the environmental impacts of fortified drinks were lower than those of milk.
Conclusions
The index based on nutrients currently obtained from milk is the most suitable one for capturing the nutritional consequences of substituting milk with PBDs in the current diets. However, the other indices can bring additional information on the possible nutritional benefits in another decision-making situation. As nutrient fortification has substantial impact on the results, the role of fortification in sustainable foods should be further evaluated and the methodological approaches to consider fortification in nLCA advanced.